1, 2‐Dihydrophosphete: A Platform for the Molecular Engineering of Electroluminescent Phosphorus Materials for Light‐Emitting Devices. Issue 31 (2nd July 2014) - Chen, Hui; Pascal, Simon; Wang, Zuoyong; Bouit, Pierre‐Antoine; Wang, Zisu; Zhang, Yinlong; Tondelier, Denis; Geffroy, Bernard; Réau, Régis; Mathey, François; Duan, Zheng; Hissler, Muriel
Abstract The discovery and molecular engineering of novel electroluminescent materials is still a challenge in optoelectronics. In this work, the development of new π‐conjugated oligomers incorporating a dihydrophosphete skeleton is reported. Variation of the substitution pattern of 1, 2‐dihydrophosphete derivatives and chemical modification of their P atoms afford thermally stable derivatives, which are suitable emitters to construct organic light‐emitting diodes (OLEDs). The optical and electrochemical properties of these new P‐based oligomers have been investigated in detail and are supported by DFT calculations. The OLED devices exhibit good performance and current‐independent CIE coordinates.